KNOWLEDGE, ATTITUDES AND PRACTICES RELATED TO PREVENTING THE TRANSMISSION OF COVID 19 AMONG SOCIAL MEDIA USERS IN INDONESIA - Boby Febri Krisdianto; Leni Merdawati; Mulyanti Roberto Muliantino; Hema Malini; Feri Fernandes; Hastoro Dwinantoaji; Januar Ramadhan; Taufik Febriyanto; Pardomuan Robinson Sihombing (UNEJ e-Proceeding, 2020)
Background: Several countries have implemented health protocols in order to prevent the spread of covid-19. One of the promotional media used by the government is social media. The effectiveness of this prevention is very much dependent on community cooperation. Knowledge, attitudes and practices of the community in preventing Covid 19 have an important role in the new normal era. Purpose The purpose of this study is to describe the trust of the Indonesian people to information on the prevention of Covid 19 on social media and public knowledge, attitudes and practices regarding prevention of the spread of COVID-19. Methods This research is a cross sectional online survey. The survey instrument consisted of respondent characteristics consisting of 5 demographic characteristics items and 5 social media use characteristics items, 13 items of trust in social media, 18 items of knowledge, 6 items of attitude and 12 items of practice. The research, which was conducted from 1 September 2020 to 25 September 2020, received 1129 responses. The questionnaire items were modified from the published paper. This research was tested statistically descriptively. Results: Most of the Indonesian people have high trust in Covid 19 prevention information on social media (mean 2.56 and standard deviation 0.55), good knowledge (mean 2.78 with standard deviation 0.60), good affective (mean 2.58 with standard deviation 0.70), good practices (mean 2.42 with a standard deviation of 0.70) regarding Covid-19 prevention. The social media trend chosen by the Indonesian people is Instagram (33.2%) Conclusion. The findings reported in this study are important because they are useful for increasing awareness of institutional and government leaders about the trust in information on social media, knowledge, attitudes, and practices of the prevention of COVID-19 in the Indonesian community. Keywords: Social media; Trustworthiness; COVID-19; Knowledge; Attitude; Practice